The Learning Leverage of Teacher Professional Training in Indonesia - Umar Abdullah (LINGUA: Jurnal Bahasa dan Sastra, 2019)
Abstract: Drawing upon Hunzicker’s (2008a, 2011) interpretive tool of learning leverage, the study aimed to find out the influence of teacher professional training, known as PLPG, on teacher learning. This study was conducted under the qualitative approach involving six high school English-language teachers. Data were collected through semi-structured interviews. The study found that the majority of the participants agreed that the rigor, reward, and risk of PLPG had boosted their motivation to learn, and thus perceived PLPG as a powerful learning experience. In particular, two teachers considered rigor (high standards and expectations) of PLPG as the most influential factor. One teacher was very much concerned about the risk of not earning certification. Three teachers counted reward as most important in their PLPG experience. This study therefore suggests that teacher professional development through teacher certification could be a powerful learning experience for teachers when it incorporates an appropriate balance of rigor, reward, and risk. Keywords: learning leverage, teacher learning, teacher professional training, teacher education Abstrak: Mengacu pada Learning Leverage Interpretive Tool yang dikembangkan oleh (Hunzicker’s (2008a, 2011), penelitian ini bertujuan untuk melihat pengaruh Pendidikan dan Latihan Profesi Guru (PLPG) terhadap pembelajaran guru. Penelitian kualitatif ini melibatkan enam orang guru Bahasa Inggris sekolah menengah. Data penelitian diperoleh melalui wawancara bebas terpimpin. Riset ini menemukan bahwa sebagian besar peserta setuju bahwa rigor, reward, dan risk PLPG memotivasi mereka untuk belajar dan mereka menganggap PLPG sebagai pengalaman belajar yang efektif. Khususnya, dua orang guru menganggap rigor sebagai faktor yang paling berpengaruh. Satu orang peserta sangat mengkhawatirkan resiko (risk) tidak lulus sertifikasi. Tiga orang peserta lainnya melihat reward sebagi faktor paling penting dalam pengalaman pembelajaran PLPG. Karena itu, riset ini merekomendasikan bahwa pengembangan profesi guru melalui program sertifikasi dapat menjadi wahana pembelajaran yang efektif bagi guru manakala program tersebut mengintegrasikan keseimbangan yang tepat antara rigor, reward, dan risk. Kata-kata kunci: learning leverage, pembelajaran guru, pengembangan profesi guru, pendidikan guru